On the methodologies and transferability of bicycle research: A perspective from outside academia - Walta, Leonie (Journal of Transport and Land Use, 2018)
Driven by an increasing concern about urban liveability, climate change, and healthy life styles, amongst others, researchers are aiming to better understand why people bicycle and what could induce them to cycle more. Given the importance of local conditions and culture, there is not just one general answer to those questions. Furthermore, there is an ongoing debate on which methodological approach delivers the most meaningful results. This commentary outlines the current position of bicycle research on the question of why people bicycle and proposes ways of moving forward.